Методологія педагогічної діяльності викладача як чинник впливу на самоорганізацію самостійної роботи майбутніх інженерів - Клочко, В. І.; Коломієць, А. А. (НТУ "ХПІ", 2015)
Процес саморозвитку майбутніх фахівців є актуальною проблемою перебудови системи освіти. Це керований процес особистісних та професійних рис студентів. Важливою умовою здійснення педагогічного керування є наявність особистісних та професійних якостей викладача (емпатія, комунікабельність, фасилятивність і інші).

The process of self-development of future specialists is an actual problem of the reconstruction of the education system. This is a managed process of personal and professional traits of the students. An important condition for the implementation of the educational management is the availability of personal and professional qualities of a teacher (empathy, communication skills, faciliating and others).
Methodology of pedagogical activity of the teacher as a factor of influence on the self-organization of independent work of future engineers
Keywords: майбутні фахівці; процес саморозвитку; перебудова системи освіти; педагогічне керування; позитивне очікування; self-organization; independent work; positive expectation